Synchronization in networks of nonlinear circuits : essential topics with MATLAB® code /: essential topics with MATLAB® code. (2018) - Frasca, Mattia; Gambuzza, Lucia Valentina; Buscarino, Arturo; Fortuna, Luigi
No abstract available